Graphitic carbon nitride nanosheets with low ON1-doping content as efficient photocatalysts for organic pollutant degradation. Issue 2 (25th January 2021) - Huang, Yan; Ning, Lichao; Feng, Zibo; Ma, Guifeng; Yang, Shuliang; Su, Yuzhong; Hong, Yanzhen; Wang, Hongtao; Peng, Li; Li, Jun
Abstract : ON1 -Doped g-C3 N4 nanosheets with low oxygen content showed a greatly enhanced photocatalytic performance for the degradation of organic pollutants. Abstract : Oxygen-doped (O-doped) graphitic carbon nitride (g-C3 N4 ) usually presents excellent photocatalytic activity compared to pristine g-C3 N4 with the common ON2 -doping. However, there are very few research studies concerned with the ON1 -doped g-C3 N4 . Herein, g-C3 N4 nanosheet samples with two different O-doping positions (ON1 and ON2 ) were prepared and characterized. Different ON1 -doping contents were achieved via the polycondensation of g-C3 N4 under different calcination temperatures for the precursor urea. Results showed that the as-prepared ON1 -doped g-C3 N4 nanosheets with an oxygen content of 2.16% demonstrated the highest photocatalytic activity in degrading rhodamine B (RhB, 10 mg L −1 ) with a degradation rate as high as 99% in 3 min under visible light irradiation, which is the best g-C3 N4 photocatalyst compared to the literature reports for RhB degradation. The improved degradation was related to the decreased oxygen content of ON1 -doped g-C3 N4 nanosheets instead of normal ON2 -doping, which was also confirmed by DFT computation.